Zagadnienie komunikacji we współczesnym handlu międzynarodowym - Kamiński, Zenon (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The importance of uniform understanding of most commonly used terms in foreign trade is beyonddispute. Therefore doubts arise as to the necessity and usefulness of translation of legal acts andother wordings used in international commerce. Special regard has been given to the meaning in otherlanguages of various terms appearing in the UN Vienna Convention on international sale of goods,and differences as compared with the approach i.a. in the Incoterms 2000 have been discussed. Thenecessity of world-wide-acceptable standards to avoid misunderstandings and disputes has beenstressed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 197-205